2015
DOI: 10.4103/2278-0203.149610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cytotoxicity of fiber reinforced composite bonded retainers and flexible spiral wires retainers in simulated high and low cariogenic environments

Abstract: Objectives:The aim of this study was to evaluate the cytotoxic effects of fiber reinforced composite bonded retainers in comparison with flexible spiral wires (FSWs) under high and low cariogenic-simulated environments using human oral fibroblasts.Materials and Methods:Four types of bonded retainers were evaluated: (1) reinforced with glass fibers: Interlig (Angelus), (2) reinforced with polyethylene fibers: Connect (Kerr), (3) reinforced with quartz fibers: Quartz Splint UD (RTD), and (4) FSW. Twenty specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Both composites exhibit approximately 100% cell viability for varying concentrations after 24 h of cell culture. For a highly concentrated solution (16 µg mL −1 ), cell viability declined to 98% after 72 h. Given that both composites exhibit approximately 100% cell viability after 24 h of culture, it may be assumed that neither is hazardous 17,22 …”
Section: Resultsmentioning
confidence: 99%
“…Both composites exhibit approximately 100% cell viability for varying concentrations after 24 h of cell culture. For a highly concentrated solution (16 µg mL −1 ), cell viability declined to 98% after 72 h. Given that both composites exhibit approximately 100% cell viability after 24 h of culture, it may be assumed that neither is hazardous 17,22 …”
Section: Resultsmentioning
confidence: 99%
“…A previous study demonstrated that these fibers were noncytotoxic, as evidenced by the absence of any adverse effects on fibroblasts from day 1 of the exposure until day 11 when the cells returned to their normal state. 24 The exceptional compatibility of E-glass can be attributed to its chemical resistance in very acidic and mildly acidic conditions. It does not undergo any potentially harmful reactions, leaching, or release of substances that could be toxic to cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the flowable composite used for impregnation and production of FRCs has shown favorable biocompatibility. 24 However, it must be applied correctly, as any leftover or unreacted monomers found to be the leading cause of cytotoxicity to fibroblasts can be minimized. 11 Therefore, the concentration and type of resin monomers are noteworthy, particularly for restorations in direct contact with the gingival tissue.…”
Section: Discussionmentioning
confidence: 99%